Framing pictures : film and the visual arts - Jacobs, Steven (Edinburgh Studies in Film, 2011)
Summary : Edinburgh Film Studies is a series of advanced textbooks which cover core aspects of film studies for undergraduate students while, at the same time, offering valuable material for the general reader and the expert. The series as a whole provide a comprehensive introduction to the subject. Each volume focuses on a key topic in film studies and is intended to produce a broad overview as well as a critical intervention. Each study, therefore, is not only informed but also analytical and controversial. Volumes are discursive, accessible and alert to recent developments in the field. They each contains suggestions for further reading, an extensive bibliography, and one or more case-study chapters in which a specific film (short, feature or documentary) is analysed in depth, with the book topic providing the wider framework.